Method for improving on-load activation voltage of zinc-silver battery

By doping and surface treatment of the negative electrode of the zinc-silver battery, the problem of low voltage caused by electrode passivation is solved, the load activation voltage and battery use efficiency are improved, and the stability of the voltage after storage of the battery is ensured.

CN119252955APending Publication Date: 2025-01-03GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411371855.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

After long-term storage of zinc silver storage batteries, passivation films are easily formed on the electrode surface, resulting in low voltage during activation, affecting the battery's use efficiency.

Method used

By performing In2O3 doping, PVA and HPMC surface treatment modification of the negative electrode of the zinc-silver battery, it is assembled into a single battery for testing and accelerated storage tests, and its load voltage and electrochemical properties are analyzed.

Benefits of technology

It improves the load activation voltage of zinc-silver batteries, extends the battery life, ensures the stability of the voltage after storage, and avoids electrode passivation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252955A_ABST
    Figure CN119252955A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving on-load activation voltage of a zinc-silver battery. The method comprises the following steps: step 1, respectively carrying out In2O3 doping, PVA surface treatment and HPMC surface treatment modification on a negative electrode of a zinc-silver reserve battery; 2, assembling the negative electrode doped with In2O3, the negative electrode subjected to PVA surface treatment, the negative electrode subjected to HPMC surface treatment and the negative electrode in the original state with the positive electrode which is not subjected to any treatment into a single battery, discharging the single battery in an environment of 20 DEG C, and testing and recording the load voltage of each group of negative electrodes; step 3, carrying out accelerated storage test on a plurality of groups of negative electrodes in different states; 4, after the accelerated storage test is completed, load voltage of each group of negative electrodes is tested and recorded; 5, testing physicochemical properties of each group of negative electrodes; step 6, performing electrochemical performance test on each group of negative electrodes; 7, analyzing a test result; when the negative electrode modified by doping In2O3 is activated in a loaded manner, the loaded voltage is increased, and meanwhile, the loaded voltage meets the requirement after the zinc-silver reserve battery is stored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-silver batteries, in particular to a method for increasing the loaded activation voltage of a zinc-silver battery. Background Art

[0002] Zinc-silver reserve battery is a one-time activated battery with high specific energy, safety, reliability and long storage life. It is used in many fields and supporting products. After the production of zinc-silver battery products is completed, they are inspected and stored in dry state. When they are needed to perform tasks, they are taken out and used. At this time, the battery is required to still meet the use requirements after long-term storage.

[0003] In the prior art, there is a related patent application that discloses a device and method for eliminating the low voltage of a zinc-silver battery during loading. The application publication number is CN 106169589A. The content is that an activator with a steel wire is connected in parallel with the positive and negative electrodes of a zinc-silver reserve battery. During the battery activation process, a current is applied between the positive and negative electrodes for a short time of discharge to eliminate the passivation film on the surface of the electrode and burn out the activator. After the battery activation time is over, when the battery is officially loaded, there will be no low voltage during loading, thereby eliminating the low voltage during battery loading and improving the stability of the working voltage.

[0004] When zinc-silver reserve batteries are stored in a dry state, the positive electrode AgO decomposes to produce Ag2O with a large resistance. At the same time, the O2 produced by the decomposition of the positive electrode makes it easy to form a passivation film on the negative electrode. When the battery is activated, it is difficult to ensure that the passivation film can be completely removed by releasing current in a short period of time, which may also lead to a relatively low battery voltage at the moment of load activation. As time goes by, the passivation film gradually thickens after the battery is stored, and the instantaneous activation voltage under load will also be very low. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for increasing the loaded activation voltage of a zinc-silver battery.

[0006] The present invention is achieved through the following technical solutions.

[0007] The present invention provides a method for increasing the loaded activation voltage of a zinc-silver battery, comprising the following steps: Step 1: performing In2O3 doping, PVA surface treatment and HPMC surface treatment modification on the negative electrode of the zinc-silver reserve battery;

[0008] Step 2: Assemble the negative electrode doped with In2O3, the negative electrode treated with PVA, the negative electrode treated with HPMC and the original negative electrode with the positive electrode not treated in any way into a single cell and discharge it in a 20°C environment, and test the load voltage of each group of negative electrodes and record it;

[0009] Step 3: Conduct accelerated storage tests on the negative electrode under different conditions;

[0010] Step 4: After the accelerated storage test is completed, the load voltage of each group of negative electrodes is tested and recorded;

[0011] Step 5: Conduct physical and chemical property tests on each group of negative electrodes;

[0012] Step 6: Conduct electrochemical performance tests on each group of negative electrodes;

[0013] Step 7: Analyze the test results.

[0014] Preferably, in the step one, In2O3 is doped into the mixed zinc powder to adjust two groups of negative electrodes with different proportions, the ratio of the mixed zinc powder and In2O3 in the first group of negative electrodes is 100 to 1; the ratio of the mixed zinc powder and In2O3 in the second group of negative electrodes is 100 to 2, and the two groups of negative electrodes doped with In2O3 in different proportions are formed into plates and then assembled with the positive electrode into a single cell for electrical performance testing.

[0015] Preferably, in step one, during the PVA surface treatment, three different concentrations of PVA are used to perform surface treatment on different negative electrodes, and the three concentrations of PVA are 0.5% PVA, 1% PVA and 4% PVA, respectively. The three groups of formed plates are immersed in a solution at a constant temperature of 30°C for one hour and then dried under natural conditions.

[0016] Preferably, in step five, an XRD test is performed on each group of negative electrodes, and the 2θ diffraction angle value of each group of negative electrodes is analyzed from the XRD spectrum, and the diffraction peak intensity of Zn in each group of negative electrodes in the spectrum is observed and analyzed.

[0017] Preferably, the diffraction peak intensity of ZnO in each group of negative electrodes in the spectrum is observed and analyzed.

[0018] Preferably, in step six, a Tafel test is performed on each group of negative electrodes, and the corrosion current in each group of negative electrodes is recorded and analyzed.

[0019] Preferably, the corrosion potential of each group of negative electrodes is recorded and analyzed.

[0020] The beneficial effects of the present invention are as follows: the negative electrode is modified by In2O3 doping, PVA surface treatment and HPMC surface treatment, and the load voltage of the negative electrode in different states is recorded, from which it can be seen that the load voltage of the negative electrode in the In2O3 doping modification is the highest, and the load voltage of the negative electrode in the PVA surface treatment is also relatively high, both of which are higher than the load voltage of the original state of the negative electrode; secondly, the negative electrodes in different states of each group are subjected to accelerated storage test, the load voltage of the negative electrode after accelerated storage is tested and recorded, and it is concluded that the load voltage of the negative electrode in the In2O3 doping modification is also the highest; then, each group of negative electrodes is subjected to XRD test and corrosion current and potential test, so that the 2θ diffraction angle value of the negative electrode in each group state is consistent with the original state of the negative electrode. The 2θ diffraction angle values ​​of the initial state are compared with those of the negative electrode in the tafel test. At the same time, the corrosion current and potential of the negative electrode in each group of states are compared with the corrosion current and potential of the original state of the negative electrode. It is concluded that the ZnO content of the negative electrode treated with HPMC surface is higher than that of other groups, and the corrosion potential is more positive, which leads to electrode passivation. The corrosion potential of the negative electrode modified by doping In2O3 shifts negatively, which does not lead to electrode passivation. The dissolution rate of the surface zinc electrode in the alkaline solution is increased, and the reaction proceeds normally. It is concluded that the load voltage of the negative electrode modified by doping In2O3 increases when it is activated with load. At the same time, it ensures that the voltage of the zinc-silver reserve battery meets the requirements after storage, and the load voltage will not decrease with time, thereby enhancing the use efficiency of the zinc-silver reserve battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a curve diagram of the unaccelerated storage loaded voltage of the seven groups of negative electrodes in different states in the step 2 of the present invention during the discharge process;

[0022] Figure 2 It is a load voltage curve diagram of the seven groups of negative electrodes in different states in step 3 of the present invention during the discharge process after the accelerated storage test for 14 years;

[0023] Figure 3 This is an XRD data diagram obtained after the XRD test is completed in the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0026] In an embodiment of the present application, a method for increasing the loaded activation voltage of a zinc-silver battery includes the following steps:

[0027] Step 1: The negative electrode of the zinc-silver reserve battery is modified by In2O3 doping, PVA surface treatment and HPMC surface treatment, so that the negative electrode with different treatments can be compared with the original state of the negative electrode.

[0028] Specifically, the mixed zinc powder and In2O3 are doped to adjust two groups of negative electrodes with different weight ratios. In the first group of negative electrodes and In2O3 doping, the ratio of mixed zinc powder and In2O3 is 100 to 1; in the second group of negative electrodes and In2O3 doping, the ratio of mixed zinc powder and In2O3 is 100 to 2.

[0029] When the PVA surface is treated again, three different concentrations of PVA are used to treat the surface of different negative electrodes. The three different concentrations of PVA are 0.5% PVA, 1% PVA and 4% PVA. The three groups of formed plates are immersed in a constant temperature solution of 30°C for one hour and then dried under natural conditions.

[0030] Finally, the concentration of HPMC was set to 0.5% HPMC for surface treatment of the negative electrode, and the formed plate was immersed in a solution at a constant temperature of 30°C for one hour, and then dried under natural conditioning.

[0031] In the embodiment of the present application, a total of seven groups of negative electrodes in different states, including the original state of the negative electrode, participate in the load activation voltage test, as shown in Table 1:

[0032] Table 1 Negative electrode status

[0033]

[0034] Step 2: Assemble the seven groups of negative electrodes in different states with the positive electrodes that have not been treated into single cells and discharge them in a 20°C environment. Test and record the load voltage of each negative electrode. The specific load voltage values ​​are shown in Table 2:

[0035] Table 2 Unaccelerated storage load voltage

[0036] Serial number Load voltage / V (1) 1.305 (2) 1.310 (3) 1.272 (4) 1.255 (5) 1.219 (6) 1.384 (7) 1.346

[0037] Combining Table 2 and Figure 1It can be concluded that the order of the load voltage from large to small is: (6)>(7)>(2)>(1)>(3)>(4)>(5), so it can be concluded that the negative electrode with a ratio of 100 to 1 of doped mixed zinc powder and In2O3 has the highest load voltage. It can also be concluded that the load voltage of the single cell doped with In2O3 and surface treated with 0.5% PVA concentration is higher than the load voltage of the single cell in its original state.

[0038] Step 3: In order to further test the value of the load voltage in the single cell after 14 years of storage, the seven groups of negative electrodes in different states were subjected to accelerated storage tests; after the test, the seven groups of negative electrodes in different states were assembled into single cells with the positive electrodes that had not been treated in any way, and then discharged in a 20°C environment, and the load voltage of each negative electrode was tested and recorded; the specific load voltage values ​​are shown in Table 3:

[0039] Table 3 Accelerated storage 14 years load voltage

[0040] Serial number Load voltage / V (1) 1.344 (2) 1.366 (3) 1.313 (4) 1.302 (5) 1.253 (6) 1.387 (7) 1.372

[0041] The load voltage after accelerated storage is combined with the load voltage from Table 3 and Figure 2 It can be seen that the order of the load voltage from large to small is: (6)>(7)>(2)>(1)>(3)>(4)>(5). Similarly, it can be concluded that the negative electrode with a ratio of 100 to 1 of In2O3 doped into the mixed zinc powder has the highest load voltage. It can also be concluded that the load voltage of the single cell doped with In2O3 and surface treated with 0.5% PVA concentration is higher than the load voltage of the single cell in its original state.

[0042] Comprehensive analysis of the two sets of data shows that before and after accelerated storage, the negative electrode with In2O3 doped in the mixed zinc powder at a ratio of 100 to 1 has the highest load voltage. This shows that a ratio of 100 to 1 between mixed zinc powder and In2O3 is best for improving the load voltage.

[0043] Step 4: In order to test the test results, in the embodiment of the present application, the physical and chemical properties of the negative electrodes in seven groups under different conditions are tested; specifically, an XRD test is performed to obtain an XRD graph.

[0044] Specific values ​​such as Figure 3 As shown in the figure, it can be concluded that the negative electrode doped with In2O3 does not show corresponding peaks in the XRD spectrum due to the small amount of addition. When 2θ is 38.99°, 43.23°, and 54.34°, they correspond to the (100), (101), and (102) crystal planes of Zn (PDF#04-0831), respectively. The intensities of these three diffraction peaks of Zn after modification are weakened. Among them, the diffraction peak intensity gradually weakens with the increase of PVA concentration and In2O3 ratio.

[0045] When 2θ is 31.77° and 34.42°, it corresponds to the (100) and (002) crystal planes of ZnO (PDF#36-1451), respectively. The intensities of these two diffraction peaks of the negative electrode treated with 0.5% HPMC are significantly higher than those of other modified states. Therefore, it can be concluded that the proportion of ZnO in the negative electrode treated with 0.5% HPMC is higher than that in the other groups.

[0046] Step 5: Electrochemical performance tests were also performed on each negative electrode. Specifically, Tafel tests were performed on seven groups of negative electrodes in different states, and the corrosion current and potential were recorded. The specific values ​​are shown in Figure 4:

[0047] Table 4 Statistics of corrosion current and potential of negative electrode in various states

[0048] Serial number <![CDATA[Corrosion current i corr (A)]]> <![CDATA[Corrosion potential E corr (V)]]> (1) 0.1216 -1.483 (2) 0.1543 -1.415 (3) 0.1599 -1.414 (4) 0.1799 -1.415 (5) 0.1396 -1.412 (6) 0.1488 -1.495 (7) 0.1280 -1.484

[0049] It can be analyzed from Table 4 that, compared with the original state, the corrosion potential of the electrode doped with In2O3 shifts negatively, and the corrosion potential and corrosion current of the negative electrode with a ratio of In2O3 doped into the mixed zinc powder of 100 to 1 are both larger; the corrosion potential of the electrode treated with PVA and HPMC surface shifts positively, and the corrosion potentials of the electrodes treated with PVA surface of different concentrations in each group are basically the same, except that the corrosion current gradually increases with the increase of PVA concentration; the corrosion current and corrosion potential of the electrode treated with HPMC surface are lower than those of other groups.

[0050] Step six: Analyze the test results. The electrode treated with In2O3 and 0.5% PVA in the negative electrode modification has a higher load voltage. After XRD test and electrode tafel test, it can be concluded that the negative electrode ZnO treated with HPMC surface accounts for more than the other states, and the corrosion potential is more positive, indicating that the addition of HPMC leads to electrode passivation, so the load voltage is the lowest; low concentration of PVA can increase the load voltage by inhibiting electrode passivation, and high concentration of PVA leads to electrode passivation; the corrosion potential of the electrode doped with In2O3 shifts negatively, indicating that the dissolution rate of the zinc electrode in the alkaline solution is increased. From each group of data, it can be concluded that the data before and after accelerated storage show that the negative electrode with a specific ratio of In2O3 doped in the mixed zinc powder of 100 to 1 can effectively increase the battery's load voltage.

[0051] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for increasing the loaded activation voltage of a zinc-silver battery, characterized in that: The following steps are involved: Step 1: The negative electrode of the zinc-silver storage battery is modified by In2O3 doping, PVA surface treatment and HPMC surface treatment respectively; Step 2: Assemble the negative electrode doped with In2O3, the negative electrode treated with PVA, the negative electrode treated with HPMC and the original negative electrode with the positive electrode not treated in any way into a single cell and discharge it in a 20°C environment, and test the load voltage of each group of negative electrodes and record it; Step 3: Conduct accelerated storage tests on the negative electrode under different conditions; Step 4: After the accelerated storage test is completed, the load voltage of each group of negative electrodes is tested and recorded; Step 5: Conduct physical and chemical property tests on each group of negative electrodes; Step 6: Conduct electrochemical performance tests on each group of negative electrodes; Step 7: Analyze the test results.

2. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 1, characterized in that: In the step 1, In2O3 is doped into the mixed zinc powder to adjust two groups of negative electrodes with different proportions. The ratio of the mixed zinc powder and In2O3 in the first group of negative electrodes is 100 to 1; the ratio of the mixed zinc powder and In2O3 in the second group of negative electrodes is 100 to 2. The two groups of negative electrodes doped with In2O3 in different proportions are formed into plates and then assembled with the positive electrode into a single cell for electrical performance testing.

3. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 1, characterized in that: In the step 1, during the PVA surface treatment, three different concentrations of PVA are used to treat the surface of different negative electrodes respectively, and the three concentrations of PVA are 0.5% PVA, 1% PVA and 4% PVA respectively. The three groups of formed plates are immersed in a solution at a constant temperature of 30° C. for one hour and then dried under natural conditions.

4. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 1, characterized in that: In the step 5, an XRD test is performed on each group of negative electrodes, and the 2θ diffraction angle value of each group of negative electrodes is analyzed from the XRD spectrum, and the diffraction peak intensity of Zn in each group of negative electrodes in the spectrum is observed and analyzed.

5. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 4, characterized in that: The diffraction peak intensity of ZnO in each group of negative electrodes in the spectrum was observed and analyzed.

6. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 1, characterized in that: In the step six, a Tafel test is performed on each group of negative electrodes, and the corrosion current in each group of negative electrodes is recorded and analyzed.

7. A method for increasing the loaded activation voltage of a zinc-silver battery as claimed in claim 6, characterized in that: The corrosion potential of each group of negative electrodes was recorded and analyzed.

Citation Information

Patent Citations

  • Elimination device of loading working voltage drop of zinc-silver battery and elimination method thereof

    CN106169589A